PENGARUH RISIKO PERUSAHAAN, INTENSITAS ASET TETAP, UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN, DAN KOMITE AUDIT TERHADAP TAX AVOIDANCE - Kumara, Nyoman Sekar Perwita Ari; Trisnawati, Rina (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research aims to test whether there is an influence of company risk, fixed asset intensity, company size, sales growth, and audit committee on tax avoidance. The population in this research is property and real estate companies listed on the Indonesia Stock Exchange in 2018 - 2022, totaling 92 companies. The number of samples in this study was 57 samples. The sampling technique uses a purposive sampling method. The research method used is quantitative with data sources in the form of secondary data. The data analysis method uses multiple linear regression analysis with SPSS version 25. The results of this research state that company risk has a negative effect on tax avoidance; fixed asset intensity, company size, and sales growth have no effect on tax avoidance; and the audit committee has a positive effect on tax avoidance